Intellectual experiments of the Greek enlightenment - Solmsen, Friedrich, 1904-1989 (Princeton, New Jersey : Princeton University Press, 1975)
Generally known for its advanced, often radical suggestions of reform in politics, religion, morality, and human behavior, the Greek Enlightenment has long been studied in terms of its doctrines and theories. To understand the environment in which the new ideas flourished and their impact, Friedrich Solmsen explores the novel intellectual methods that developed during the period. A variety of new modes of thought was introduced at this time or, if known before, was applied with delight in experimentation. Among those that Friedrich Solmsen examines are new methods of argumentation: persuasion aimed at the control of man's emotions; Utopian speculation; experiments with language; and the emergence of a secular psychology and its use in the reconstruction of human motives and historical events. Concentrating on the work of nonphilosophical authors such as the historian Thucydides and the tragedian Euripides, the author presents a portrait of a restless and spirited age engaged in an adventure of reason.Originally published in 1975.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Preface -- Bibliographical Note -- Abbreviations -- Introduction -- I. Argumentation -- II. Persuasion -- III. Utopian Wishes and Schemes of Reform -- IV. Experiments with the Greek Language -- V. Empirical Psychology and Realistic Generalization -- VI. Rational Reconstruction -- Conclusion -- Subject Index -- Index
Includes indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Philosophy, Ancient; Reason; Sophists (Greek philosophy); Philosophie ancienne; Raison; Sophistes grecs; reason; PHILOSOPHY -- History & Surveys -- Ancient & Classical; Philosophy, Ancient; Reason; Sophists (Greek philosophy)